2020
DOI: 10.1038/s41699-020-00164-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging, three-dimensional interaction spectroscopy, and friction anisotropy of atomic-scale ripples on MoS2

Abstract: Theory predicts that two-dimensional (2D) materials may only exist in the presence of out-of-plane deformations on atomic length scales, frequently referred to as ripples. While such ripples can be detected via electron microscopy, their direct observation via surface-based techniques and characterization in terms of interaction forces and energies remain limited, preventing an unambiguous study of their effect on mechanical characteristics, including but not limited to friction anisotropy. Here, we employ hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Local modifications in lattice, topography, and mechanical properties were understood by transmission electron microscopy (TEM) and atomic force microscopy (AFM) studies. [12][13][14] Furthermore, scanning tunneling microscopy (STM) experiments revealed the local electronic density of states and a bandgap reduction at the wrinkle. [15,16] However, the optical and excitonic properties of nanoscale wrinkles, that is, the most intriguing properties for device applications, have not yet been investigated in details due to the diffraction-limited spatial resolution of conventional PL spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Local modifications in lattice, topography, and mechanical properties were understood by transmission electron microscopy (TEM) and atomic force microscopy (AFM) studies. [12][13][14] Furthermore, scanning tunneling microscopy (STM) experiments revealed the local electronic density of states and a bandgap reduction at the wrinkle. [15,16] However, the optical and excitonic properties of nanoscale wrinkles, that is, the most intriguing properties for device applications, have not yet been investigated in details due to the diffraction-limited spatial resolution of conventional PL spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring by contact mode AFM the contaminated vdW surfaces reveals a domain structure in the torsion (friction) signal, which cannot be linked to the features in the topography channel and is also present in atomically smooth regions (see FigS3 and FigS8b-c). The origin of these frictional domains [12][13][14][18][19][20][21][22][23] was not conclusively clari ed to date, which hinders the possibility to willingly manipulate or remove them. Our ndings establish a direct causal link between the self-organized stripes of the adsorbed alkane layer and the friction anisotropy (Fig4a-b).…”
Section: Anisotropic Friction Domainsmentioning
confidence: 99%
“…Gallagher et al 13 proposed that a contamination layer could be the cause for the widely reported anisotropic friction on graphene and hBN, but the nature of the molecules forming the ordered surface cover could not be determined. Many groups reported anisotropic friction domains on various vdW materials: monolayer to few layer graphene 13,14,18−21 , hexagonal boron nitride (hBN) 13 , molybdenum disul de (MoS 2 ) 12,21,22 and tungsten disul de (WS 2 ) 23 . In all these reports, the friction anisotropy exhibits common properties, such as a domain structure, C2 rotation symmetry in each domain, 60° angles between the symmetry axes of adjacent domains, despite the differences in the chemical or mechanical properties of the host surface.…”
Section: Introductionmentioning
confidence: 99%
“…The other prominent features in the STM images are the ripples in the silica layer. Such ripples are characteristic of atomically thin 2D materials but typically occur over a much wider length scale. , The ∼4 nm wavelength is beyond the range of the DFT calculations; however, we would expect to see a very low-frequency out-of-plane vibrational mode that could be associated with this distortion. In Figure a, there are two bands that cross Γ horizontally at 135 cm –1 that correspond to tetrahedra tilting on opposite sides of the bilayer that could lead to an out-of-plane distortion.…”
mentioning
confidence: 93%